Strategi Menangani Tamu Check in saat Kamar Penuh: Studi Kasus Salahsatu Hotel di Kota Balikpapan - Rustika, Ranti; Gafur, Abdul (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2024)
The XYZ Balikpapan is one of the esteemed hotels in Balikpapan that is widely chosen by the community as a place for accommodation or events on certain occasions. Consequently, numerous room reservations are made, leading to full occupancy. Therefore, the XYZ Balikpapan Hotel requires a strategy for handling guest check-ins during peak occupancy. This research aims to explore the strategies employed by the XYZ Balikpapan Hotel in managing guest check-ins and the challenges encountered during peak occupancy. The research methodology employed in this study is descriptive qualitative research, utilizing data collection techniques such as observation, interviews, and documentation. In this research, there are stages of analysis, starting from data reduction, data presentation, and conclusions The findings of this study reveal several challenges faced by hotel guests during the check-in process at the XYZ Balikpapan Hotel. These challenges include guests waiting for rooms to be ready for occupancy due to frequent full occupancy, inadequate human resources for room cleaning, and sudden guest requests upon check-in. The XYZ Balikpapan Hotel addresses these challenges by implementing various strategies, including organizing exhibitions for micro, small, and medium-sized enterprises (UMKM), optimizing the kid's corner, fostering good cooperation between receptionists and housekeeping staff, providing welcome drinks and snacks, conducting courtesy calls, assigning room numbers in the system, preparing registration card forms, and providing room keys. It is expected that these strategies will effectively